Reputation for cooperation: contingent benefits in alliance activity - Arend, Richard J. (Strategic Management Journal, 2009)
We model the two‐firm alliance as an iterated prisoners' dilemma game with an exit option and test several theoretical predictions in experimental studies regarding the effect of reputation information. Following the literature, we hypothesize that reputation benefits cooperation; however, our experimental results instead show that reputation decreases cooperation. A contingency explains this result while remaining consistent with the general proposition of reputation as beneficial in games of incomplete information. Implications include a recommendation for when to invest in reputation and whether the lemon's market story is applicable to alliance‐related inefficiencies. Copyright © 2009 John Wiley & Sons, Ltd.